Rereading Sayyid Quṭb’s Islamism and Political Concept of al-Ḥākimiyyah: A Critical Analysis - Muktafi; Al Haidary, Abdullah Haq; Zamzami, Mukhammad (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This article analyzes Islamism and Sayyid Quṭb’s political concept of al-Ḥākimiyyah. According to Qutb, Islamism is a political structure and a part of the Muslim faith. Employing a theoretical perspective of the functions of interpretation proposed by Jorge J. E. Gracia, this analysis found out that Quṭb’s al-Ḥākimiyyah is the most vital concept behind the phenomenon around global religious fundamentalism. This theory promotes a political structure believed to be emanated from God’s will and not merely from the people’s sovereignty. The idea of al-Ḥākimiyyah ignores any laws and systems of values made by human being. In other words, people who attempt to go against the theory will be considered rebelling against the Qur’an and Hadith and assumed to be the enemy. By analyzing through the functional theory of text interpretation of Quṭb’s ideology, this article challenges the narrative of Quṭb’s Islamism and al-Ḥākimiyyah, which presents a very arrogant face of Islam and cannot accept differences in thought. Islamism, through the framework of al-Ḥākimiyyah, is a political structure, not a faith structure. Nevertheless, this kind of Islamism is not merely political, but what Bassam Tibi called religionized politics. Quṭb’s ideological proposal is a real example of the religious doctrine of global fundamentalism. Quṭb’s ideas are the specific interpretation of Islam but not necessarily Islam: it is a political ideology different from Islam’s teaching.